1997
DOI: 10.1021/bi961745d
|View full text |Cite
|
Sign up to set email alerts
|

Study of Structure and Function of Recombinant Pea Root Plastid Porin by Biophysical Methods

Abstract: Pea root plastid porin (Fischer et al. (1994) J. Biol. Chem. 269, 25754-25760), which belongs to the family of mitochondrial (eukaryotic) porins, was expressed in Escherichia coli in high amounts using the pQE expression system. The recombinant protein was reconstituted into lipid bilayer membranes, and its characteristic properties were compared to those of the native porin isolated from pea root plastids. No significant difference was found between the native and the recombinant form when the protein was pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 43 publications
2
13
0
Order By: Relevance
“…Therefore, the SDSinduced conformational changes of class 3 protein are characterized by the generation of a partially unfolded state as demonstrated by the SDS-dependent generation of a molecular species exhibiting faster electrophoretic migration than that observed for the native trimeric state. These results suggest that such species might populate the in vivo folding pathways of porins, particularly in the case of class 3 protein, and supports the notion that porins may undergo folding/unfolding through monomeric intermediates as suggested before for other membrane proteins including porins (54). In fact, the effects of SDS may be envisioned as the initial step on the folding pathway of class 3 protein in which a partially unfolded intermediate inserts into the membrane and eventually assumes its final ␤-sheet oligomeric conformation.…”
Section: Sds-induced Conformational Changes Of Classsupporting
confidence: 87%
“…Therefore, the SDSinduced conformational changes of class 3 protein are characterized by the generation of a partially unfolded state as demonstrated by the SDS-dependent generation of a molecular species exhibiting faster electrophoretic migration than that observed for the native trimeric state. These results suggest that such species might populate the in vivo folding pathways of porins, particularly in the case of class 3 protein, and supports the notion that porins may undergo folding/unfolding through monomeric intermediates as suggested before for other membrane proteins including porins (54). In fact, the effects of SDS may be envisioned as the initial step on the folding pathway of class 3 protein in which a partially unfolded intermediate inserts into the membrane and eventually assumes its final ␤-sheet oligomeric conformation.…”
Section: Sds-induced Conformational Changes Of Classsupporting
confidence: 87%
“…Both modeling and artificial bilayer experiments revealed that the S193E variant opens and closes less frequently than does the wild-type [43] although the open state conductances are similar (3.7 and 3.9 nS, respectively, [44]). In this case, the N-terminal methionine is not present in the native form [45], but presumably remains in the recombinant one.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…This archaeal lipid forms very densely packed and stable planar bilayers, suitable for these measurements [81]. Low concentrations of sterol may added to the lipid mixture used to create the bilayer [80] or added to the detergent solubilized porin [44] to encourage insertion of the protein into the bilayer. While sterol is a component of native membranes, its interactions with DPhPC may be subtly different, and influence the lipid environment of the VDAC.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…For example, adapting unfolding and refolding protocols that consider the presence of lipids that are naturally present in the functional unit (e.g. cholesterol (De Pinto et al, 1989b) or ergosterol for Neurospora crassa (Freitag et al, 1982) VDAC) or of non-ionic detergents in the protein solution (Engelhardt et al, 2007;Koppel et al, 1998;Popp et al, 1997;Ujwal et al, 2008) can be considered. Indeed, because of the artificial process of refolding in the presence of detergents, the proposed VDAC1 structure has been questioned (Colombini, 2009).…”
Section: Vdac Purificationmentioning
confidence: 99%